Multi-proxy evidence from bogs for environmental change in Ireland over the last 1,200 years - Cole, Edwina E. (Trinity College (Dublin, Ireland). Department of Botany, 2001)
In order to understand recent and future climate change, it is necessary to document how climates have varied in the past. Literature and research concerning climate change of the last 1,200 years, namely the Medieval Warm Period, Little Ice Age and 20th Century Warming, are discussed. Ireland has a wealth of palaeoecological records based on its vegetation since the last ice age which provide some very good records of past climates and their associated impacts. Unfortunately many lack the temporal resolution necessary to investigate small climatic changes on centennial to millennial scales and to provide information on these and the environmental changes that may have occurred as a result of these climatic changes. This thesis presents the results of a high resolution multiproxy record of climate and its environmental impact over the last 1,200 years from three sites in Ireland. These sites follow a gradient of increasing wetness across the country from east to west. Vegetation changes and anthropogenic impacts are also provided from these sites for this time period. The various methods used in this investigation include pollen analysis, fungal spore and testate amoebae analysis, charcoal analysis, loss on ignition and dating in the form of radiocarbon dating and tephrochronology. These methods are explained and discussed in Chapter III and the results presented in Chapters IV to VIII.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin